2006
DOI: 10.1111/j.1600-0609.2006.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypogammaglobulinemia with a selective delayed recovery in memory B cells and an impaired isotype expression after rituximab administration as an adjuvant to autologous stem cell transplantation for non‐Hodgkin lymphoma

Abstract: Conclusions: Abnormal repertoires and impaired isotype expression are seen in patients with common variable immunodeficiency, these data suggested that rituximab after APBSCT can affect not only the B-cell quantities, but also the recovery of the B-cell repertoires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 25 publications
4
38
0
2
Order By: Relevance
“…It is expected that the reconstituted B-cell population after a transplant remains significantly depleted of memory CD27 ϩ B cells for as long as 2 years after single dose of rituximab. 4 It would be interesting to see how many EBV reactivations and PTLPDs have been observed after rituximab containing conditioning regimen for B-cell malignancies from a larger database. 5 Rituximab infusion given 2 months after total lymphoid irradiation (TLI)-ATG showed excellent disease control with minimal graft-versus-host disease (GVHD) without any detrimental effects on engraftment or infection and no EBV reactivation reported.…”
mentioning
confidence: 99%
“…It is expected that the reconstituted B-cell population after a transplant remains significantly depleted of memory CD27 ϩ B cells for as long as 2 years after single dose of rituximab. 4 It would be interesting to see how many EBV reactivations and PTLPDs have been observed after rituximab containing conditioning regimen for B-cell malignancies from a larger database. 5 Rituximab infusion given 2 months after total lymphoid irradiation (TLI)-ATG showed excellent disease control with minimal graft-versus-host disease (GVHD) without any detrimental effects on engraftment or infection and no EBV reactivation reported.…”
mentioning
confidence: 99%
“…12 Lymphoma patients who receive rituximab as adjuvant or maintenance following autologous HSCT, however, have been reported to have an increased risk of developing severe and long-lasting hypogammaglobulinemia despite quantitative CD19 þ B-lymphocyte recovery. [20][21][22][23] Laboratory studies in patients with lymphoma or alloantibodies before kidney transplantation have shown a delayed recovery of CD19 þ /CD27 þ B-memory cells and impaired isotype expression following rituximab therapy as seen in patients with common variable immunodeficiency, suggesting that rituximab can affect not only B-cell quantities but also the recovery of functional B-cell repertoires and differentiation into plasma cells. 20,21,24,25 Little is known of the consequences of rituximab therapy on B-lymphocyte depletion and recovery in patients with PTLD following allogeneic HSCT, particular in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Laboratory studies in patients with lymphoma or alloantibodies before kidney transplantation have shown a delayed recovery of CD19 þ /CD27 þ B-memory cells and impaired isotype expression following rituximab therapy as seen in patients with common variable immunodeficiency, suggesting that rituximab can affect not only B-cell quantities but also the recovery of functional B-cell repertoires and differentiation into plasma cells. 20,21,24,25 Little is known of the consequences of rituximab therapy on B-lymphocyte depletion and recovery in patients with PTLD following allogeneic HSCT, particular in pediatric patients. Although incubation of B cells with anti-CD20 antibody depletes normal circulating B cells and has variable effects on cell cycle progression and signaling, the detailed biologic functions of CD20 remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A B-és a T-sejtek felszínén is megnőhet a CD95 expresszió, a memória típusú T-sejtek aránya növekszik, míg a naív T-sejteké pedig csökken [7]. Ezek az eltérések (IgD -CD27 + memória B-sejtek hiánya, hypogammaglobulinaemia, fokozott CD95 expresszió, naív T-sejtek arányának csökkenése) összességében a common variábilis immundefficienciához (CVID) hasonló állapotot tükröznek, és az immunrendszer éretlenségére utalnak [6,7,9].…”
Section: Ezek Alapján Határoztuk El Hogy Felmérjük a Klinikánkon 200unclassified